USAHA GURU BK DALAM MENGATASI PESERTA DIDIK YANG MENGALAMI KESULITAN BELAJAR DI SMA NEGERI 2 KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Jefrianto, Jefrianto (Bimbingan dan Konseling, 2014)
This research is motivated by the presence of students violating the school rules , especially at a time of teaching and learning takes place , the symptoms that look like : learning tasks can not be done well , do not repeat the material provided by the teacher in the previous lesson , interfere friends while studying , late for class , exit / clearance before learning ends , or do not get in on a particular subject . The purpose of this study describes : Efforts have been made to overcome the difficulties BK teachers of learners . This research is descriptive quantitative research . In the entire study population of students of class X and class XI who have difficulty in learning at SMAN 2 Koto XI Tarusan the number 81 . Sampling using sampling saturated . The technique used to analyze the data is the percentage techniques . The results of this study found that the efforts that have been made in overcoming difficulties BK teachers of learners SMAN 2 Koto XI Tarusan in general are in both categories with a percentage of 64.20 %.